IMPLEMENTATION OF ONLINE AND OFFLINE LEARNING DURING THE COVID-19 SITUATION - Fauzan, Fauzan; Iryanti, Elma; Arifin, Fatkhul (Lentera Pendidikan : Jurnal Ilmu Tarbiyah dan Keguruan, 2023)
This study aims to describe the learning process and analyze the impacts of online and offline learning at SDN Makassar 01 Pagi during the Covid-19 period. The descriptive qualitative method was used in this study with three instruments, interview guidelines, observation sheets, and documentation. The subjects were teachers of class IV of SDN Makassar 01 Pagi. The data were analyzed using Miles’ & Huberman’s analysis consisting of three steps, namely data reduction, data display, and conclusions drawing/verification. The results indicated that SDN Makasar 01 Pagi implemented asynchronous online learning using WhatsApp and Google Classroom. At the same time, offline learning was carried out in that school with limited students and learning time by implementing health protocols and the media used, such as books, worksheets, teaching aids and media in the school environment. In addition, online and offline learning had positive and negative impacts. Abstrak: Penelitian ini bertujuan untuk mendeskripsikan proses pembelajaran dan menganalisis dampak pembelajaran online dan offline di SDN Makassar 01 Pagi pada masa Covid-19. Penelitian ini menggunakan metode deskriptif kualitatif dengan tiga instrumen, yaitu pedoman wawancara, lembar observasi, dan dokumentasi. Subjek penelitian adalah guru kelas IV SDN Makassar 01 Pagi. Analisis data menggunakan analisis Miles & Huberman yang terdiri dari tiga langkah yaitu reduksi data, display data, dan penarikan kesimpulan/verifikasi. Hasil penelitian menunjukkan bahwa SDN Makasar 01 Pagi menerapkan pembelajaran online asinkron menggunakan WhatsApp dan Google Classroom. Sementara itu, pembelajaran luring dilaksanakan di sekolah dengan siswa dan waktu belajar yang terbatas serta menerapkan protokol kesehatan.Media yang digunakan seperti buku, LKS, alat peraga dan media di lingkungan sekolah. Selain itu, pembelajaran online dan offline memiliki dampak positif dan negatif.